The Epl1 and Sm1 proteins from Trichoderma atroviride and Trichoderma virens differentially modulate systemic disease resistance against different life style pathogens in Solanum lycopersicum - Salas-Marina, Miguel A.; Isordia-Jasso, María I.; Islas-Osuna, María A.; Delgado-Sánchez, Pablo; Jiménez-Bremont, Juan F.; Rodríguez-Kessler, Margarita; Rosales-Saavedra, María T.; Herrera-Estrella, Alfredo; Casas-Flores, Sergio (Frontiers in Plant Science, 2015)
Fungi belonging to the genus Trichoderma, commonly found in soil or colonizing plant roots, exert beneficial effects on plants, including the promotion of growth and the induction of resistance to disease. T. virens and T. atroviride secrete the proteins Sm1 and Epl1, respectively, which elicit local and systemic disease resistance in plants. In this work, we show that these fungi promote growth in tomato (Solanum lycopersicum) plants. T. virens was more effective than T. atroviride in promoting biomass gain, and both fungi were capable of inducing systemic protection in tomato against Alternaria solani, Botrytis cinerea, and Pseudomonas syringae pv. tomato (Pst DC3000). Deletion (KO) of epl1 in T. atroviride resulted in diminished systemic protection against A. solani and B. cinerea, whereas the T. virens sm1 KO strain was less effective in protecting tomato against Pst DC3000 and B. cinerea. Importantly, overexpression (OE) of epl1 and sm1 led to an increase in disease resistance against all tested pathogens. Although the Trichoderma WT strains induced both systemic acquired resistance (SAR)- and induced systemic resistance (ISR)-related genes in tomato, inoculation of plants with OE and KO strains revealed that Epl1 and Sm1 play a minor role in the induction of these genes. However, we found that Epl1 and Sm1 induce the expression of a peroxidase and an α-dioxygenase encoding genes, respectively, which could be important for tomato protection by Trichoderma spp. Altogether, these observations indicate that colonization by beneficial and/or infection by pathogenic microorganisms dictates many of the outcomes in plants, which are more complex than previously thought.